Optimasi Pembuatan dan Karakterisasi Ukuran Partikel Superparamagnetic Iron Oxyde Nanoparticles - Wulandari, Anggita Dipika; Yusuf, Mubarika Sekarsari; Husniyah, Laelatul (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Superparamagnetic Iron Oxide Nanoparticles (SPION) are iron-based nanoparticles gaining attention in the medical field due to their ability to be magnetically guided and their biocompatibility. This study aimed to explore how different homogenization speeds affect the size, distribution, and stability of SPION synthesized through the co-precipitation method. Three formulations were prepared using homogenization speeds of 1000 rpm, 3000 rpm, and 6000 rpm. The resulting particles were analyzed using Dynamic Light Scattering (DLS) to determine particle size, polydispersity index (PDI), and zeta potential. The results showed that Formula 2 (3000 rpm) produced the smallest and most evenly distributed particles (305,2 nm) with good stability. Formula 3 (6000 rpm) had a higher zeta potential, its particle size was larger and distribution less uniform. Formula 1 (1000 rpm) yielded large but more uniformly distributed particles. The results of this study show moderate homogenization speed offers the best conditions for producing SPION that are small, stable, and suitable for biomedical applications. Formula 2 shows the most promise for future development in drug delivery or magnetic hyperthermia therapies